2021
DOI: 10.3390/ijerph19010319
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking as a Maladaptive Coping Style in the Pandemic Scenario: What Worked and What Did Not for Facing This New Stressor

Abstract: The spread of COVID-19 and its related confinement measures were important stressors for a large part of the global population, with massive effects on both physical and mental health. Assessing how individuals coped with such a stressor and which strategies were effective is one of the main challenges for psychological research. In this study, we aimed to investigate the coping strategies implied during the COVID-19 lockdown and their effectiveness. We recruited 374 Italian participants through convenience sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…However, more advanced analyzes did not confirm the existence of such a relationship. Thus, although immersion into the world of social relations may have a salutary effect on psychological wellbeing, several studies ( 30 ) show that this effect may be quite opposite. The ambiguity of the obtained results prompts to conduct further research.…”
Section: Discussionmentioning
confidence: 99%
“…However, more advanced analyzes did not confirm the existence of such a relationship. Thus, although immersion into the world of social relations may have a salutary effect on psychological wellbeing, several studies ( 30 ) show that this effect may be quite opposite. The ambiguity of the obtained results prompts to conduct further research.…”
Section: Discussionmentioning
confidence: 99%
“…Contributing to this T A B L E 6 K-means clustering, three cluster solutions for perceived helpfulness, cluster centers debate, we found that (dis)engagement coping purposes were integral to one another in the management of linked thoughts and emotions-combined in our hybrid Reappraisal and Distancing scalereflecting the complexity of managing thoughts and emotions related to health-related stressors as found in other service contexts (e.g., Fisher et al, 2021;Zheng & Montargot, 2021). Consumers may, thus, be able to utilize online health services as disengagement coping with more positive value when dealing with thoughts and emotions than previously found (e.g., Buizza et al, 2022;Simione et al, 2022).…”
Section: Theoretical Implicationsmentioning
confidence: 94%
“…For example, in the case of a breast cancer diagnosis, consumers may use wishful thinking to give themselves a “break” from the current situation (Varni et al, 2012). There is evidence that, in the context of complex services, engagement coping can lead to a reduction in perceived stress and positive psychological wellbeing; whereas disengagement coping can lead to heightened stress levels and psychological distress (Buizza et al, 2022; Simione et al, 2022). However, we should be cautious in making such generalizations.…”
Section: Conceptual Foundationsmentioning
confidence: 99%
“…Comparing Italy to other European countries, we observed that the second wave of the pandemic seemed to have had a lower impact on mental health [16]. Emotional regulation and coping strategies were also protective factors, because they allowed for a reappraisal of the situation, and they modified the intensity and the duration of negative emotions [17,18]. Literature suggested that most people were resilient, but that it is also important to understand which factors came into play to promote habituation [19].…”
Section: Introductionmentioning
confidence: 89%